Morphodynamic Foundations of Sumer. - Liviu Giosan; Reed Goodman (PLoS ONE)
Economic mechanisms behind the emergence of ancient Sumer remain unavoidably speculative and should benefit from a better understanding of their environmental context. Abundance sustaining increased social complexity during the Uruk period (c. 6,000-5,200 y BP) has been traditionally ascribed to pastoralism, trade, and/or resource diversity. However, contemporary agricultural surpluses are hard to explain before adoption of large-scale irrigation systems. Here we use high-resolution satellite-based topography and paleoenvironmental proxies from a new drill core at Lagash/Tell Al Hiba, together with previous geological and archaeological data, to reconstruct the morphodynamic evolution of coastal Sumer. We propose that tidal irrigation offers a plausible jumpstarting mechanism for high-yield, diversified agriculture providing an impetus for urbanization. As access to sea was restricted by delta build-up and tides shifted with the advancing deltaic coast, intensified reliance on mercurial river regimes eventually led to the expansive fluvial irrigation network of Early Dynastic city-states. By positioning coastal morphodynamics as a pivotal factor in urbanization and political ecology, we underscore the intricate interconnections between naturally evolving systems and collective human agency.